Emanuel Bastl, Leader of the Opera Ensemble in Olomouc (1928-1932) - Hasikova, Miriam (Musicologica Olomucensia, 2016)
The existence and development of theatre institutions has always been determined by the current political and particularly by economic situation, the social stratification of the inhabitants and the audience, by the development of the media as well as by the artistic capacity of the country in the discussed era. These influences manifested themselves in the theatre of Olomouc, which was going through the crisis and consequent transformation at the turn of the 1920's and 1930's. The most representative constituent of the theatre in the interwar era, the opera ensemble, was nearly dissolved while the operetta ensemble was at its peak. This text depicts the development of the opera in the Olomouc theatre, headed by Emanuel Bastl during 1928-1932, and also considers the overall metamorphosis of the theatre as an institution in Czechoslovakia during the given period.
Keywords: Opera; Olomouc; Czech theatre; repertoire; tours; financial crisis; Emanuel Bastl; Antonin Drasar; Stanislav Langer